Hubungan Pengetahuan, Stimulasi dan Status Gizi dengan Perkembangan Bicara dan Bahasa pada Balita di Posyandu Atsiri Permai Kabupaten Bogor Tahun 2022 - Inggit Norhadewi; Maryam Syarah; Siti Rafika Putri (Indonesia Journal of Midwifery Sciences, 2023)
Introduction: Speaking and language are children's abilities to respond to sounds heard, convey their wishes, and follow orders given. They are also very important indicators in life to communicate. Objectives: This study aims to determine the relationship between knowledge, stimulation, and nutritional status with speech and language development in toddlers at Posyandu Atsiri Permai, Bogor Regency. Method: The research method used is quantitative analysis with a cross-sectional approach, namely a research design in which measurements or observations of stimulants are carried out at one time or at a time. The samples used were 77 samples based on solvency calculations. data were collected using a questionnaire and analyzed using the chi-square test. Result: the results of the above study can be concluded that: From 77 respondents in this study, it was found that mothers with less knowledge were 44 respondents or 57.1%, mothers with attitudes that did not stimulate toddlers were 40 respondents or 51.9% and toddlers with poor nutritional status there are 41 respondents or 53.2%. Conclusion: This makes the variables Knowledge, Stimulation and Nutritional Status have a significant relationship to speech development in toddlers with the result that the p-value of Knowledge is 0.000, the p-value of Stimulation is 0.009 and the p-value of Nutritional Status is 0.005.